Breeding and age-structure seasonality in Carollia brevicauda and other frugivorous bats (Phyllostomidae) in cloud forests in the Venezuelan Andes - Molinari, Jesús; Soriano, Pascual J. (THERYA, 2014)
The most universal adaptations of tropical frugivores to the seasonal rhythms of fruiting involve their annual breeding cycles. In bats, these cycles typically follow a pattern termed bimodal polyestry, consisting in the production of one offspring per female twice during the breeding season. We use data gathered along 29 years to show that, in cloud forests in the Venezuelan Andes, the breeding cycles of Carollia brevicauda and other frugivorous phyllostomid bats (eigth species of the genera Sturnira, Artibeus, Dermanura, Enchisthenes, and Platyrrhinus) conform to bimodal polyestry, with a high interspecific synchronization and a low interannual variability. We analyze the adaptive significance of this pattern in terms of three hypothetical variables: demand, consumption, and supply of food sources, explicitly concluding that the seasonality of fruit production, resulting from the average rainfall regime, is the ultimate factor causing bimodal polyestry. The constancy in the seasonal schedule of breeding and concomitant fluctuation of age proportions, both in the bat populations studied under natural conditions, and in captive Carolliacolonies maintained under year-round uniform conditions, suggests presence of an endogenous component in the annual breeding cycles of frugivorous phyllostomids. To conclude, we argue that the seasonality of fruiting is also likely to be the proximate environmental factor modulating these cycles, irrespective of whether it does so indirectly as a time cue entraining endogenous rhythms, or directly as a limiting factor determining whether bat breeding and population growth are possible. Key words: Artibeus, bimodal polyestry, circannual rhythms, Dermanura, Enchisthenes, environmental cues, Platyrrhinus, reproductive strategies, Sturnira, tropical seasons.